Evolution of virulence in facultative pathogens - Pandey, Aakash (Kansas State University, 2022)
In addition to infecting hosts, facultative pathogens can grow independent of hosts in environmental reservoirs. These diverse ecological settings can result in novel life-history trait correlations and trade-offs. The consequence of such trait correlations on virulence evolution is largely understudied, both theoretically and empirically. In this study, I examined how reproduction in reservoirs influences disease dynamics and virulence evolution. I used mathematical models to determine how pathogen growth rate and environmental carrying capacity influence epidemiological outcomes. Further, I used the adaptive dynamics framework to examine the evolutionary dynamics of facultative pathogens under potential trade-offs between transmission and virulence, shedding and virulence, and reservoir persistence and virulence. I then performed critical function analysis to generalize the results independent of specific trade-off assumptions. I found that diverse virulence strategies, sometimes resulting from evolutionary bistability or evolutionary branching conditions, are expected for facultative pathogens. In these pathogens, adaptation to environmental reservoirs can influence virulence within host. I tested this idea using Stenotrophomonas maltophilia, an emerging opportunistic human pathogen. Previous research found that a type IV secretion system plays a role in both host-pathogen interactions and competition with other bacteria. I experimentally evolved four strains of S. maltophilia (JV3, JCMS, R551-3, and K279a) that vary in their virulence on the host Caenorhabditis elegans. I found that these strains also vary in the degree to which they use interference mechanisms in competition with Escherichia coli MG1655. Multiple independent populations initiated with highly virulent strains JV3, JCMS, and R551-3 show reductions in both virulence and their competitive ability. These observations suggest a positive correlation between the virulence and the interspecies competitive ability of the pathogen. Genomic comparison of the ancestral and evolved lines shows that several reduced virulence strains have mutations in their type IV secretion system operon. I also show that both virulence and competitive ability are reduced in a [Delta]virB10 mutant compared to the wild-type and complemented strains. Similarly, I found that the previously identified effector proteins of type IV secretion system 14245 and 14255 also have dual function in both virulence and interference competition. To test whether the presence of a competitor has any effect on virulence evolution, I evolved the highly virulent JV3 with and without competitor E. coli MG1655. Results show that the virulence of population lines evolved without the competitor E. coli is reduced to a greater extent than of those population lines evolved in the presence of E. coli. These results suggest that coincidental selection for interference competition against heterologous bacteria can contribute to the virulence of S. maltophilia. Taken together, this research highlights the importance of environmental adaptation to shaping the consequences that facultative pathogens have on hosts.
Keywords: Virulence evolution; Facultative pathogens; Coincidental selection; Community assembly; Trade-offs